2000
DOI: 10.1038/sj.onc.1203252
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of ERT(ESX/ESE-1/ELF3), an ets-related transcription factor, induces endogenous TGF-β type II receptor expression and restores the TGF-β signaling pathway in Hs578t human breast cancer cells

Abstract: The epithelium-speci®c transcription factor, ERT/ESX/ ESE-1/ELF3, binds to the TGF-b RII promoter in a sequence speci®c manner and regulates its expression. In this study, we investigated whether ERT could regulate endogenous TGF-b RII expression in Hs578t breast cancer cells. Analyses of the Hs578t parental cell line revealed low RII mRNA expression and resistance to the growth inhibitory eects of TGF-b. Infection of this cell line with a retroviral construct expressing ERT induced higher levels of endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…The best known candidate is the gene encoding for TGF-b RII, as several studies have clearly shown that Elf3 can bind to the promoter and regulate transcription of the TGF-b RII gene. [27][28][29][37][38][39] Moreover, it has also been reported that Elf3À/À mice express reduced protein levels of TGF-b RII in the developing small intestinal epithelium when compared with Elf3 þ / þ mice. 26 Although TGF-b RII is a potent inhibitor of cell proliferation, it is very important for the induction of epithelial cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best known candidate is the gene encoding for TGF-b RII, as several studies have clearly shown that Elf3 can bind to the promoter and regulate transcription of the TGF-b RII gene. [27][28][29][37][38][39] Moreover, it has also been reported that Elf3À/À mice express reduced protein levels of TGF-b RII in the developing small intestinal epithelium when compared with Elf3 þ / þ mice. 26 Although TGF-b RII is a potent inhibitor of cell proliferation, it is very important for the induction of epithelial cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, Elf3 has been shown to be involved in regulating the expression of genes involved in controlling epithelial cell proliferation and differentiation during embryonic/fetal development and oncogenesis. 17,26,30,37,38,[42][43][44] Therefore, the delayed kinetics of cell proliferation/mitosis and Clara cell reconstitution observed within the bronchiolar airway epithelium of Elf3À/À mice is more likely because of changes in gene expression for proteins involved in regulating epithelial cell proliferation and/or differentiation during repair after naphthalene-induced Clara cell ablation. The best known candidate is the gene encoding for TGF-b RII, as several studies have clearly shown that Elf3 can bind to the promoter and regulate transcription of the TGF-b RII gene.…”
Section: Discussionmentioning
confidence: 99%
“…50 In contrast, overexpression of ESE-1 in human breast cancer cells has been shown to induce endogenous TGF-b RII expression, resulting in restitution of the TGF-b signaling pathway along with a significant reduction in resistance to the growth inhibitory effects of TGF-b. 32 …”
Section: Ese-1 In Mammary Gland Development and Breast Cancermentioning
confidence: 99%
“…34 In human colonic epithelial cells, ESE-1 has also been shown to regulate gene expression of the proinflammatory cytokine, macrophage inflammatory protein-3a (MIP-3a). 39 Another group has previously reported that CR6-interacting factor 1 (Crif1) plays an essential role in Elf3-mediated intestinal development by functioning as a transcriptional co-activator of Elf3 during terminal differentiation of the 25,30 Mouse bronchiolar airway epithelium 42 Mouse embryonal carcinoma cell line (F9) 33,35,37 Human embryonic kidney cell line (HEK 293T) 33,35,37 Human hepatoblastoma cell line (HepG2) 31 Human gastric cancer cell line (SNU-620) 31 Human colon cancer cell line (RKO) 34 Human breast cancer cell lines (SK-BR3, Hs578t) 31,32 Human cervical cancer cell line (HeLa 229) 31,33 Macrophage inflammatory protein-3a (MIP-3a)m Human colonic epithelial cell line (Caco-2) 39 Small proline-rich protein 1B (SPRR1B)m Primary human tracheobronchial epithelial cells 41 Human bronchial epithelial cell line (BEAS-2B) 41 Human lung adenocarcinoma epithelial cell line (NCI-H441) 41 Epithelium-specific ETS transcription factor-3 (ESE-3)m Human bronchial epithelial cell line (BEAS-2B) 44 Human lung carcinoma cell line (A549) 44 Interleukin-6 (IL-6)m Mouse lung tissue 44 Primary mouse airway epithelial cells 47 Primary mouse bone marrow-derived dendritic cells 47 Human bronchial epithelial cell line (BEAS-2B) 47 Interleukin-12 (IL-12)m Primary mouse bone marrow-derived dendritic cells 47 Lysozyme (LYZ)m Primary human bronchial airway epithelial cells 46 Human lung carcinoma cell line (A549) 46 Human lung mucoepidermoid carcinoma-derived cell line (NCI-H292) 46 Human lung adenocarcinoma epithelial cell line (NCI-H441) …”
Section: Ese-1 In Regulating Epithelial Cell Differentiation During Imentioning
confidence: 99%
See 1 more Smart Citation